Foreign Policy of Madagaskar under the Leadership of Andry Rajoelina: Analysis of Domestic Determinants - Krisna Silawa; Achmed Sukendro; Bayu Setiawan (Journal of Islamic World and Politics, 2022)
Madagascar is one of the countries with the best geographical location in Sub-African, facing not only the Indian Ocean but also the Mozambique Strait. With the limitations it faces, the foreign policy made by Madagascar’s leaders can be a good strategy in articulating the interests of this country. In an article belonging to Bojang A.S, one of the determinants of foreign policy-making is domestic. It will guide the authors in analyzing the domestic determinants of Madagascar in determining its policy under the leadership of Andry Rajoelina. This article was written using a secondary-qualitative method by collecting and analyzing secondary data from accredited books, scientific articles, and news. This study compared existing data with guidelines (Bojang A.S.) and analyzed how these determinants produce Madagascar’s foreign policy. In the end, this article describes eight domestic determinants influencing Madagascar’s foreign policy under Rajoelina’s leadership.